2023
DOI: 10.1093/bjd/ljad010
|View full text |Cite
|
Sign up to set email alerts
|

Guselkumab for hidradenitis suppurativa: a phase II, open-label, mode-of-action study

Abstract: Background Effectiveness of available biologics for the treatment of hidradenitis suppurativa (HS) is limited. Additional therapeutic options are highly needed. Objective To investigate the efficacy and mode of action of guselkumab (an anti-IL-23p19 monoclonal antibody) 200 mg s.c., every four weeks for 16 weeks in HS patients. Methods An open label, multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Of participants receiving guselkumab, 45% and 50.8% met HiSCR at week 16, which was not significantly higher than the placebo group (38.7%). Prior to the phase 2b trial, an open-label phase 2a trial studied guselkumab 200 mg SQ every 4 weeks in 22 patients [ 100 ]. A total of 13 out of 20 (65%) achieved HiSCR, while 7 out of 20 (35%) achieved HiSCR75 at week 16.…”
Section: Resultsmentioning
confidence: 99%
“…Of participants receiving guselkumab, 45% and 50.8% met HiSCR at week 16, which was not significantly higher than the placebo group (38.7%). Prior to the phase 2b trial, an open-label phase 2a trial studied guselkumab 200 mg SQ every 4 weeks in 22 patients [ 100 ]. A total of 13 out of 20 (65%) achieved HiSCR, while 7 out of 20 (35%) achieved HiSCR75 at week 16.…”
Section: Resultsmentioning
confidence: 99%
“… 19 , 20 The literature also includes several reports concerning HS, specifically encompassing two recent phase 2 studies and multiple case reports or series. Dudink et al 21 conducted a 24-week open-label, multicenter, phase IIa trial, enrolling 20 patients and divided into 16 weeks of treatment followed by an 8-week follow-up. The primary endpoint was achieving HiSCR at week 16.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 The literature also includes several reports concerning HS, specifically encompassing two recent phase 2 studies and multiple case reports or series. Dudink et al 21 a follow-up four weeks after treatment cessation. Secondary endpoints involved IHS4 and AN count at these same time points.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results from two phase III trials have demonstrated sustained efficacy and safety of secukinumab on HS for up to 52 weeks of treatment, when given every 2 weeks [16]. On the contrary, phase II studies did not provide strong evidence to support the efficacy of IL-23 inhibitors on HS, putting into question the central role of the IL-23/T-helper 17 axis in HS pathophysiology [17, 18].…”
Section: Discussionmentioning
confidence: 99%